Internal tide generation by abyssal hills using analytical theory. Issue 11 (26th November 2013) - Melet, Angélique; Nikurashin, Maxim; Muller, Caroline; Falahat, S.; Nycander, Jonas; Timko, Patrick G.; Arbic, Brian K.; Goff, John A.
<x xml:space="preserve">Abstract</x> [1] Internal tide driven mixing plays a key role in sustaining the deep ocean stratification and meridional overturning circulation. Internal tides can be generated by topographic horizontal scales ranging from hundreds of meters to tens of kilometers. State of the art topographic products barely resolve scales smaller than ∼10 km in the deep ocean. On these scales abyssal hills dominate ocean floor roughness. The impact of abyssal hill roughness on internal‐tide generation is evaluated in this study. The conversion of M2 barotropic to baroclinic tidal energy is calculated based on linear wave theory both in real and spectral space using the Shuttle Radar Topography Mission SRTM30_PLUS bathymetric product at 1/120° resolution with and without the addition of synthetic abyssal hill roughness. Internal tide generation by abyssal hills integrates to 0.1 TW globally or 0.03 TW when the energy flux is empirically corrected for supercritical slope (i.e., ∼10% of the energy flux due to larger topographic scales resolved in standard products in both cases). The abyssal hill driven energy conversion is dominated by mid‐ocean ridges, where abyssal hill roughness is large. Focusing on two regions located over the Mid‐Atlantic Ridge and the East Pacific Rise, it is shown that regionally linear theory predicts an increase of the energy flux due to abyssal hills of up to 100% or 60% when an empirical correction for supercritical slopes is attempted. Therefore, abyssal hills, unresolved in state of the art topographic products, can have a strong impact on internal tide generation, especially over mid‐ocean ridges.